2017
DOI: 10.1093/neuonc/nox017
|View full text |Cite
|
Sign up to set email alerts
|

Blocking MIR155HG/miR-155 axis inhibits mesenchymal transition in glioma

Abstract: Our results demonstrate that the MIR155HG/miR-155 axis plays a critical role in facilitating glioma progression and serves as a prognostic factor for patient survival in glioblastoma. High-throughput screening indicated that the MIR155HG/miR-155 axis inhibitor NSC141562 may be a useful candidate anti-glioma drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
104
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 38 publications
8
104
0
Order By: Relevance
“…In this report, we analyzed the expression of MIR155HG in various cancers and paracancer or normal tissues, and analyzed the relationship between MIR155HG expression and OS, DFS and staging, consistent with Wu's finding that MIR155HG was associated with poor tumor prognosis in glioma . As reported, the expression of MIR155HG was significantly higher in cancer than paracancer in KIRC, and MIR155HG was associated with poor OS .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In this report, we analyzed the expression of MIR155HG in various cancers and paracancer or normal tissues, and analyzed the relationship between MIR155HG expression and OS, DFS and staging, consistent with Wu's finding that MIR155HG was associated with poor tumor prognosis in glioma . As reported, the expression of MIR155HG was significantly higher in cancer than paracancer in KIRC, and MIR155HG was associated with poor OS .…”
Section: Discussionsupporting
confidence: 80%
“…In this report, we analyzed the expression of MIR155HG in various cancers and paracancer or normal tissues, and analyzed the relationship between MIR155HG expression and OS, DFS and staging, consistent with Wu's finding that MIR155HG was associated with poor tumor prognosis in glioma. 10 As reported, the expression of MIR155HG was significantly higher in cancer than paracancer in KIRC, 26 and MIR155HG was associated with poor OS. 27 GO and KEGG analysis in these types of tumors showed that mRNAs co-expressed with MIR155HG were mostly enriched in immune-related functions and immune-related pathways, which indicated that MIR155HG may be related to immunity.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Several studies have reported that lncRNA MIR155HG plays key roles in the development of myeloproliferative disorders, leukemia, lymphoma, and glioma [40][41][42]. lncRNA MIR155HG can suppress lymphoma by regulating the activity of NF-κB and mesenchymal genes [42].…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that MIR155HG/miR-155 blockade could inhibit mesenchymal transition in glioma. 12 In this study, we measured MIR155HG expression in PC tumor tissue, adjacent normal tissue, cancer cell lines, and a normal pancreatic cell line. We found that higher MIR155HG expression was positively linked to the poor prognosis of the patients.…”
Section: Introductionmentioning
confidence: 99%